Evaluation of a novel brain tissue oxygenation probe in an experimental swine model - Orakcioglu, Berk; Sakowitz, Oliver; Neumann, Jan-Oliver; Kentar, Modar; Unterberg, Andreas; Kiening, Karl (Neurosurgery, 2010)
BACKGROUND: - Cerebral microdialysis, cerebral blood flow, and cerebral oxygenation (PbrO2) measurements using intraparenchymal probes are widely accepted as invasive diagnostic monitoring for early detection of secondary ischemia. - OBJECTIVE: - To evaluate a novel PbrO2 probe for continuous and quantitative oxygenation assessment compared with the existing gold standard PbrO2 probe. - METHODS: - In 9 pigs, 2 PbrO2 probes (Neurovent-TO vs Licox) were implanted into the subcortical white matter. An intracranial pressure probe was inserted contralaterally. The PbrO2 probes were tested during (1) baseline measurements followed by (2) hyperoxygenation (fraction of inspired oxygen [Fio2] = 1.0), medically induced (3) hypo- and (4) hypertension, (5) hyperventilation, (6) tris-hydroxymethylaminomethane application, and (7) hypoxygenation (Fio2 < 0.05). For statistical analyses, Bland-Altman plots were used. - RESULTS: - The Neurovent-TO probe is easy to handle and does not need a specific storage or calibration. Bland-Altman analyses revealed good comparability of both technologies under baseline conditions (meandiff 2.09 mm Hg, standard deviation 0.04 mm Hg, range 1.98-2.20 mm Hg), but measurement dynamics during hyperoxygenation (Fio2 = 1.0) revealed significantly different profiles, eg Neurovent-TO probe reached up to 1.53-fold higher PbrO2 values than the Licox probe. During hypoxygenation (Fio2 < 0.05), the Neurovent-TO probe detected the hypoxic level of 8.5 mm Hg 1.5 minutes earlier than did the Licox probe. All other maneuvers showed similar responses in both technologies. - CONCLUSION: - The Neurovent-TO PbrO2 device comparably measures PbrO2 under most conditions tested compared with the Licox device. The Neurovent-TO is more sensitive to rapid Fio2 changes. Further studies are necessary to clarify these differences. It is questionable whether existing knowledge of Licox tissue oxygenation, ie, hypoxic threshold, can be directly transferred to the Neurovent-TO.